Robert Boyle, the Great Experimenter, - Kuslan, Louis I.; Stone, A. Harris (Prentice-Hall, 1970)
The life of the seventeenth-century scientist best known for his analysis of pressure and volume in gases and for his example to fellow scientists in sharing his discoveries with them.
Keywords: Boyle; Robert; 1627-1691; Chemists; Children's literature; dept.che; dept.nhstc; faculty_collection